Rancang bangun multimedia interaktif pembelajaran IPS menggunakan model discovery learning berbantuan power point untuk meningkatkan kemampuan berpikir kreatif siswa sekolah dasar - Surbakti, Rinda Ersada; Altaftazani, Deden Herdiana; Nurfurqon, Faridillah Fahmi (IKIP Siliwangi, 2025)
This study aims to develop interactive multimedia proclamation of Indonesian independence assisted by power point class V elementary school. This type of research is development (Research and Development) following the steps of Borg and Gall.Â The subjects used in this study were grade V students at Setiawarga Elementary School, with a limited number of tests of 8 students and an extensive test of 34 students. The data analysis techniques used are qualitative and quantitative descriptive techniques. The results of this development research show that interactive multimedia assisted by power points is feasible to be used as a learning medium after carrying out material validation tests and media with results of 3.6 are included in the